BICARBONATE DOSING AT DIFFERENT BLOOD PH LEVELS IN METABOLIC ACIDOSIS, ITS RELEVANCE AND OUTCOME- A SINGLE-CENTERED PROSPECTIVE STUDY.: sodium bicarbonate, metabolic acidosis, pH - Taye, Mrinal Kanti; Deori, Kamal Chandra; Sarma, Dipak Kumar; Ahmed, Ali Asgor (Student’s Journal of Health Research Africa, 2023)
Background: Acute acidemia is a frequently observed condition in intensive care units. Intravenous sodium bicarbonate is one possible modality of treatment along with IV fluid and treating the primary cause. Most authors advocate bicarbonate therapy at an arterial pH of ≤ 7.1 but some advocate as early as when blood pH level starts falling below 7.2. This cut-off level remains a controversy. This study aimed to administer sodium bicarbonate in metabolic acidosis at different blood Ph levels and observe its effects on patients’ ABG and outcomes. Methods: The target was to maintain arterial pH of 7·20 and above. The comparison was made based on biochemical and clinical outcomes in two different groups where the group I with a blood pH. of < 7.2 and group II with a blood pH of < 7.1. Results: In the present study on day 2 pH increased from 7·16 ± 0.0453 to 7.27 ± 0.056 in group I and from 6.82 ± 0.0944 to 6.85 ± 0.0448 in group II. Hco3 increased from 8.9 ± 2.82 to 14.8 ± 3.46 in group I and from 3.9 ± 3.48 to 4.9 ± 3.8 in group II. Group I showed better correction of acidosis and bicarbonate level on day 2. Higher bolus dosages are required in group II and still insignificant rise in bicarbonate or change in pH. Conclusion: Preemptive sodium bicarbonate administration at a blood pH of 7.2 and bicarbonate level <15 rather than waiting for pH to fall below 7.1 has shown better primary outcomes in patients with severe metabolic acidemia. Its effects on mortality have not been evaluated. Whether sodium bicarbonate infusion could influence the outcome must be evaluated more in future trials. Additional investigations evaluating therapeutic interventions could be of significance within the cohort of individuals experiencing metabolic acidosis in the ICU.